Sobreposição de imagens de termografia e ressonância magnética: uma nova modalidade de imagem médica tridimensional - Sanches, Ionildo José (2009)
Infrared (IR) imaging is a noninvasive diagnostic technique that allows the examiner to evaluate and quantify changes on skin surface temperature. Since changes over the human body surface temperature are continuous, it is difficult to associate anatomical details, as well to associate skin temperature with internal structures or organs. Though providing significant information to clinical diagnosis, this technique does not allow evaluating anatomical details of the imaged region. In this work it is presented a new image fusion method for combining 3D Magnetic Resonance Images (or Computed Tomography) and 2D thermal images. The result is a 3D thermographic imaging that can improve medical diagnosis of certain human diseases, such as peripheral vascular disease, diabetic foot, breast and thyroid tumors,sinusitis, cephalalgia, rheumatic disorder and others inflammations process, i.e., diseases that can be diagnosis through the body surface thermal mapping. In the development of this interdisciplinary work of Biomedical Engineering, the knowledge of Digital Image Processing, Computer Graphics, Machine Vision, Computer Programming, Radiology, Medical Imaging and Thermography, was necessary, interacting with areas of Medicine,Computer Science and Electrical Engineering. First, magnetic resonance images (MRI) or computed tomography (CT) from region of interest are acquired. In a second experiment, a set of IR images is acquired. From the MRI or CT data, 2D projections are generated in the same direction/orientation of the tomographic planes. Then, the generated projections and the IR images are registered. Next, the registered IR images set is combined and projected over the 3D-MRI or 3D-CT. The result is a fused image that combines the information contents from two different medical images modalities. The excellent results obtained with the new methodology demonstrate that it can aid medical diagnosis.